ANTIOXIDANT ACTIVITY PROFILING OF RED BAJAKAH TAMPALA (Spatholobus littoralis Hassk) FRACTIONS USING THE DPPH RADICAL SCAVENGING METHOD - Amanda, Nathasya Gracya; Sari, Ghani Nurfiana Fadma; Novita, Mega; Marlina, Dian (Berita Biologi, 2025)
Indonesia’s rich biodiversity harbors numerous plants with medicinal properties, including Red Bajakah Tampala (Spatholobus littoralis Hassk.), which has long been used in traditional medicine for its therapeutic benefits. Despite its promising ethnomedicinal reputation, scientific validation of its antioxidant potential remains limited. This study aims to evaluate the antioxidant properties of Red Bajakah Tampala and identify key bioactive compounds responsible for its bioactivity. The plant's antioxidant capacity was assessed using the DPPH assay, and the chemical composition was analyzed through phytochemical screening and thin-layer chromatography (TLC). The ethyl acetate fraction exhibited the strongest antioxidant activity, with an IC₅₀ value of 12.87 ppm, followed by the n-hexane fraction (24.08 ppm) and the water fraction (57.23 ppm). Phytochemical screening revealed the presence of flavonoids, tannins, triterpenoids, phenols, and saponins, which contribute to the plant's antioxidant effects. These findings provide scientific evidence supporting the traditional use of Red Bajakah Tampala as a natural antioxidant, with implications for its potential use in therapeutic and cosmetic applications. Further research into the molecular mechanisms and practical applications of Bajakah-based formulations is recommended.